2018
DOI: 10.1038/s41557-018-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Design of catalysts for site-selective and enantioselective functionalization of non-activated primary C–H bonds

Abstract: C-H functionalization represents a promising approach for the synthesis of complex molecules. Instead of relying on modifying the functional groups present in a molecule, the synthetic sequence is achieved by carrying out selective reactions on the C-H bonds, which traditionally would have been considered to be the unreactive components of a molecule. A major challenge is to design catalysts to control both the site- and stereoselectivity of the C-H functionalization. We have been developing dirhodium catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 50 publications
0
86
0
1
Order By: Relevance
“…In 2008, Che and co‐workers showed that a sterically encumbered Rh‐porphyrin catalyst demonstrates high primary selectivity in carbenoid transfer reactions (Figure a) . Most recently, the Davies group reported a new dirhodium catalyst that is highly effective for the functionalization of primary C−H bonds with high levels of site‐ and enantioselectivity via [Rh]=CR 2 intermediates . By altering the sterics of the carboxylate ligands, site‐selectivity can be tuned to prefer either tertiary, secondary or primary C−H bonds…”
Section: Figurementioning
confidence: 99%
“…In 2008, Che and co‐workers showed that a sterically encumbered Rh‐porphyrin catalyst demonstrates high primary selectivity in carbenoid transfer reactions (Figure a) . Most recently, the Davies group reported a new dirhodium catalyst that is highly effective for the functionalization of primary C−H bonds with high levels of site‐ and enantioselectivity via [Rh]=CR 2 intermediates . By altering the sterics of the carboxylate ligands, site‐selectivity can be tuned to prefer either tertiary, secondary or primary C−H bonds…”
Section: Figurementioning
confidence: 99%
“…After immobilization on the silica surface,t he active site of the catalyst 3a would open toward the silica support (entry b, Figure 2), where the surface species might interact with the active site or hinder the substrate accessibility.T hus,w e decided to move forward with the linker located on ring B,as its equatorial position is conserved in other catalyst geometries in the tetracarboxylate family,m aking it the optimal anchor site for all known TPCP-based dirhodium catalysts. [13,14]…”
Section: Forschungsartikelmentioning
confidence: 99%
“…The Chiral COD ligands 1 and 2 have shown considerable promise but their synthesis requires a multistep synthesis and a resolution. 4b This has led to the synthesis of other skipped cyclic dienes as chiral ligands, [4][5][6] including a number of C2 symmetric ligands 3-6. However, all require a multistep synthesis and most involve a racemic synthesis followed by resolution [4][5][6].…”
Section: Cfmentioning
confidence: 99%
“…4b This has led to the synthesis of other skipped cyclic dienes as chiral ligands, [4][5][6] including a number of C2 symmetric ligands 3-6. However, all require a multistep synthesis and most involve a racemic synthesis followed by resolution [4][5][6]. In this paper we describe an enantioselective C-H functionalization method for the direct synthesis of C2 symmetric COD derivatives 7, with four stereogenic centers.…”
Section: Cfmentioning
confidence: 99%